Appropriate Water and Nitrogen Regulation Improves the Production of Wolfberry (Lycium barbarum L.) - Yalin Gao; Jinghai Wang; Yanlin Ma; Minhua Yin; Qiong Jia; Rongrong Tian; Yanxia Kang; Guangping Qi; Chen Wang; Yuanbo Jiang; Haiyan Li (Agronomy, 2024)
Wolfberry (Lycium barbarum L.) production in arid and semi-arid areas is drastically affected by the low utilization rate of soil and water resources and the irrational application of water and nitrogen fertilizers. Thus, this study explored a high-yielding, high-quality, and efficient irrigation and nitrogen regulation model to promote the production efficiency of wolfberry and rational utilization of water and land resources in arid and semi-arid areas. We compared and analyzed the effects of different soil water treatments (the upper and lower limits of soil water were estimated as the percentage of soil water content to field water capacity (θf), with the following irrigation regimen: adequate irrigation (W0, 75–85% θf), mild water deficit (W1, 65–75% θf), moderate water deficit (W2, 55–65% θf), and severe water deficit (W3, 45–55% θf)) and nitrogen levels (no nitrogen (N0, 0 kg·ha−1), low nitrogen (N1, 150 kg·ha−1), moderate nitrogen (N2, 300 kg·ha−1), and high nitrogen (N3, 450 kg·ha−1)) on the growth, physiology, and production of wolfberry. The results showed that water regulation, nitrogen application level, and their interaction significantly affected plant height and stem diameter growth amount (p < 0.05). Additionally, the relative chlorophyll content of wolfberry leaves first increased and then decreased with increasing nitrogen levels and water deficit. The average net photosynthetic rate (Pn), stomatal conductance (gs), intercellular carbon dioxide concentration, and transpiration rate (Tr) reached the highest values in plants exposed to W0N2 (19.86 μmmol·m−2·s−1), W1N1 (182.65 mmol·m−2·s−1), W2N2 (218.86 μmol·mol−1), and W0N2 (6.44 mmol·m−2·s−1) treatments, respectively. Pn, gs, and Tr were highly correlated with photosynthetically active radiation and water vapor pressure difference (goodness-of-fit: 0.366–0.828). Furthermore, water regulation and nitrogen levels exhibited significant effects on the yield and water- (WUE), and nitrogen-use efficiency (NUE) (p < 0.01), and their interactions exhibited significant effects on the yield, WUE, and nitrogen partial productivity of wolfberry plants (p < 0.05). Moreover, the contents of total sugar, polysaccharides, fats, amino acids, and proteins were the highest in W1N2, W1N2, W1N2, W2N3, and W0N2 treatments, respectively, which were increased by 3.32–16.93%, 7.49–54.72%, 6.5–45.89%, 11.12–86.16%, and 7.15–71.67%, respectively. Under different water regulations (except for the W3 condition) and nitrogen level treatments, the net income and input–output ratio of wolfberry were in the order W1 > W0 > W2 > W3 and N2 > N3 > N1 > N0. The TOPSIS method also revealed that the yield, quality, WUE, NUE, and economic benefits of wolfberry improved under the W1N2 treatment, suggesting that WIN2 might be the most suitable irrigation and nitrogen regulation model for wolfberry production in regions with scarce land and water resources such as the Gansu Province and areas with similar climate.